THE FUNCTIONS OF SPEECH AND POLITENESS STRATEGY IN CLASSROOM INTERACTION - Raudhatul Haura (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The application of character education in the materials’ of students’ activities at school was occurred when the qualities of three aspects of education changed. Three aspects here are cognitive, affective, and psychomotor which look to the knowledge improvement, behavior, and skill based on education pillars consequently with the realization of knowledgeable and characterized person. These categories of the functions of speech and politeness strategy always used by the teacher inleading the student to do their activities through the teaching learning process in the classroom. This study was conducted to find out the kind of functions of speech applied and politeness strategy used by the English teacher in the classroom interaction. The setting of the study was class XII and class X of SMK Negeri 3 Banjarmasin. The subject of this study was an English teacher. The data were collected by observation, and documentation. The data taken from three meetings of the teacher’s teaching schedules. The analysis of the functions of speech and politeness strategy in the classroom interaction is an analysis of the transcription of teacher’s speech in the class. This is similar with the way people analyze other transcription in general. Based on the findings, the teacher gives positive results toward this research. Teacher applied all those categories of the functions of speech needed by students to be knowledgeable person. And the teacher almost used positive politeness strategy in his teaching to shape up a politer characterized person. For the next researchers who are interested in the same topic, it is suggested to conduct a research about the analysis of the functions of speech and politeness strategy of the teacher’s speech applied in different school. The result of such studies can help the teacher leads the students’ learn in the classroom interaction more effective and politer for future learner.Key Words : Classroom Interaction, The Functions of Speech, and Politeness Strategy.